1986
DOI: 10.1172/jci112587
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte-mediated protection against Pseudomonas aeruginosa infection in granulocytopenic mice.

Abstract: BALB/c mice immunized with Pseudomonas aeruginosa immunotype 1 polysaccharide develop protective T cell immunity to bacterial challenge. In vitro, T cells from immunized mice kill P. aeruginosa by production of a bactericidal lymphokine. The present study demonstrates that adoptive transfer of T cells from immunized BALB/c mice to granulocytopenic mice resulted in 97% survival on challenge with P. aeruginosa, compared with 17% survival with adoptive transfer of T cells from nonimmune BALB/c mice. This protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…For example, these authors have shown that adoptive transfer of T cells from mice immunized with P. aeruginosa to granulocytopenic mice resulted in nearly 100% survival upon challenge with P. aeruginosa (12). Similar findings have been reported by others (3).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…For example, these authors have shown that adoptive transfer of T cells from mice immunized with P. aeruginosa to granulocytopenic mice resulted in nearly 100% survival upon challenge with P. aeruginosa (12). Similar findings have been reported by others (3).…”
supporting
confidence: 81%
“…Early studies by Markham and coworkers (8,12) suggest that T cell-mediated immune responses are protective against P. aeruginosa infections. For example, these authors have shown that adoptive transfer of T cells from mice immunized with P. aeruginosa to granulocytopenic mice resulted in nearly 100% survival upon challenge with P. aeruginosa (12).…”
mentioning
confidence: 99%
“…The data presented herein strongly suggest that IL-2-activated T cells are capable of attacking C. neoformans and directly mediating anticryptococcal activity without MHC restriction. Other investigators have demonstrated that splenic CD8+ T cells, obtained from mice immunized with Pseudomonas aeruginosa polysaccharide antigen, secrete a bactericidal lymphokine (27)(28)(29). The bactericidal effect occurred in the absence of Ab or complement and did not require phagocytic cells.…”
Section: Discussionmentioning
confidence: 99%
“…These include neutrophils (1), macrophages (21,22), NKT cells (NKTs) (23), NK cells (24), dendritic cells (25), T cells (26,27), and B cells (28,29). We attempted to examine whether IRF3 regulates immune cell infiltration into the lung in response to P. aeruginosa infection.…”
Section: Irf3 Is Required For the Recruitment Of Neutrophils And Macrmentioning
confidence: 99%